Configuraciones de masculinidad en los bailes al estilo huapanguero merequetengue en Guanajuato: Una aproximación queer desde la autoetnografía - Sánchez Pérez, José Javier; Bieletto-Bueno, Natalia (El Colegio de México A.C., 2019)
This study analyzes the participation of men and their performance of masculinity in the social practice of dancing Huapanguero merequetengue, in the Mexican state of Guanajuato. Through a “dense description” I identify three different models of masculinity as performed by dancers through bodily conducts. In the second section, I use the (auto)ethnographic method to present a queer interpretation of socio-affective dynamics developed in and through the dance in the huapango merequetengue. Finally, we debate the importance of a queer perspective in highlighting the role of subjectivity in research.